Functional study of CYP90A1 and ALDH3F1 gene obtained by transcriptome sequencing analysis of Brassica napus seedlings treated with brassinolide - Gan, Qingqin; Luan, Mingbao; Hu, Maolong; Liu, Zhongsong; Zhang, Zhenqian (Frontiers in Plant Science, 2022)
Sclerotinia disease and weeds of Brassica napus greatly reduce crop yield. However, brassinolides can improve plant resistance to sclerotinia diseases and herbicides. In this study, the effects of brassinolide on the occurrence, physiological indexes, yield, and gene expression of Fanming No. 1 seeds under sclerotinia and glufosinate stress were investigated. The results showed that soaking with 0.015% brassinolide for 6 h had the best effect, reducing the incidence of sclerotinia by 10%. Additionally, in response to glufosinate stress at the seedling stage, the enzyme activities of CAT and SOD increased by 9.6 and 19.0 U/gFW/min, respectively, and the soluble sugar content increased by 9.4 mg/g, which increased the stress resistance of plants and the yield by 2.4%. LHCB1, fabF, psbW, CYP90A1, ALDH3F1, ACOX1, petF, and ACSL were screened using transcriptome analysis. The key genes ALDH3F1 and CYP90A1 were identified, and an overexpression vector was constructed and transferred to Zhongshuang 11 (Brassica napus). After glufosinate treatment, the transgenic plants became resistant to glufosinate, and the expression levels of the ALDH3F1 and CYP90A1 genes were 1.04–2.39-fold of the control. The expression level of the antibacterial Sclerotinia disease gene ATG3 in the transgenic plants was 3.46-fold as high as the control. These results indicate that these two key genes may exert resistance to sclerotinia and glufosinate, promoting research on the molecular mechanisms of rape resistance breeding and the selection of new varieties.